Втомна міцність сплаву AlSi10Mg, отриманого шляхом адитивного виробництва: ефекти постобробки - Волошко , Світлана Михайлівна; Мордюк , Богдан Миколайович; Васильєв , Михайло Олексійович; Ворон , Михайло Михайлович (Physico-technological Institute of Metals and Alloys, 2024)
Additive manufacturing and, in particular, 3D-printing of metals and alloys has been actively developing in recent years. More and more complex parts can be produced with the involvement of more alloys. One of the most common and universal methods of 3D-printing is a selective laser melting (SLM). In turn, one of the most common and widely used alloys for SLM is the AlSi10Mg. It belongs to the class of cast alloys and is widely used in many industries due to its high specific strength, corrosion resistance, low coefficient of thermal expansion and low cost. For most additively manufactured metal parts, an important problem that needs to be solved is the provision of sufficient fatigue strength, which is associated with a relatively high defectivity of the product surfaces. The article is devoted to the review of methods of postprocessing of SLM-printed parts, made of AlSi10Mg alloy, which can increase their fatigue strength. It is noted that, in addition to the quality of the surface, the main reasons for the alloys reduced tensile strength include residual stresses caused by point overheating and cooling of metal microvolumes during the parts formation. Heat treatment, in particular – low-temperature annealing for stress relief at 250 °C with subsequent cooling in water, leads to an increase in fatigue strength by 18 %, and T6 hardening according increases the load limit by 20–40 MPa. This is explained by the silicon particles spheroidization. Hot isostatic pressing reduces the porosity of samples, as well as residual stress and homogenizes the structure, but also leads to a decrease in microhardness, yield strength, and fatigue strength. Sandblasting surface treatment by using a mixture of aluminum, silicon and zirconium oxides helps to reduce surface roughness by one and a half to two times, almost completely removes surface porosity and creates compressive stresses, which in turn increases fatigue strength. The perspective of ultrasonic surface treatment of 3D-products was also noted. It has a similar effect to sandblasting surface treatment, but it seems to be more effective.